Treatment of Hypertriglyceridemia with Aggressive Continuous Intravenous Insulin - Abigail Hoff; Kara Piechowski (Frontiers Media S.A., 2021)
Purpose: Severe hypertriglyceridemia requiring hospitalization for intravenous insulin to lower triglycerides and prevent complications of pancreatitis is becoming an increasing problem with little consensus treatment evidence. This is the largest case series to date to evaluate this under-studied area of literature. The objective of this study was to determine the average time to triglyceride lowering less than 500 mg/dL. Methods: This was a retrospective case series from March 2018 to March 2020 at a single rural academic medical center. 23 patients were included who received weight-based intravenous insulin at 0.1 units/kg/hour through a hypertriglyceridemia management order-set over a two-year period. Results: The median triglyceride level at initiation of the insulin infusion was 3759 mg/dL with an interquartile range of 5555. The median time to a triglyceride level less than 1000 mg/dL and 500 mg/dL was 45 hours (1.8 days) and 75 hours (3.1 days) respectively. Patients remained on intravenous insulin for a median of 60 hours (2.5 days). Conclusions: In this largest case series to date evaluating the use of intravenous insulin for the treatment of hypertriglyceridemia, a weight-based insulin infusion demonstrated reduction of triglyceride levels to less than 1000 mg/dL in approximately 2 days and less than 500 mg/dL in approximately 3 days.